Hirarki Kebutuhan Tokoh dalam Novel Malik & Elsa Karya Boy Candra - Sasdita Mailana; Sri Yanuarsih; M. Imron Abadi (FKIP, Universitas Palangka Raya, 2024)
Literary work is the only work of art that can represent the life of the writer and someone else in various forms so that it is related to h Likewise, novels are able to describe the broad and complex reality of human life to offer valuable lessons or morals for their readers. This study aims to describe aspects of the character hierarchy and offer an interpretation of the basic needs for survival of the characters through a literary psychology approach which can be used as an alternative to literary studies. The data source is the Malik & Elsa novel published by PT Transmedia Distributor. The focus of his research is the hierarchy of needs of figures with the theory launched by Maslow, the theory is named Abraham Maslow's hierarchy of needs t The formulation of the problem discusses physiological needs, a sense of security, belonging and love, and self-esteem. The research method used is descriptive-qualitative. Data collection techniques are reading, analysis and corpus techniques. The results showed that (1) Malik's physiological needs were met when he won the guessing game with Elsa. (2) The safety needs needed by Malik, in financial form. The aspect of feeling secure is fulfilled by working as a porter in the market. (3) Malik needs a love connection, in the form of love and affection from the opposite sex, namely Elsa. The sense of love and belonging between the two characters is fulfilled. However, due to caste differences between the two, they could not unite. (4) The esteem needs of Malik's character continue his college education.